(untitled) (Journal of Education and Development, 2020)
The present study aimed to examine the impact of Virtual Writing Tutor (VWT) software on the academic writing skills of Year 1 Omani EFL students in the College of Applied Science, (CAS)-Sohar and their attitudes towards using VWT software to enhance their academic writing skills. The sample consisted of 35 students in the control group and 35 in the experimental group (Total N= 70) who were enrolled in the English for Academic Purposes (ENAP1002) course at CAS-Sohar. The data collection tools included pre-test and post-test for the two groups, and attitude scale for the experimental group. The findings of the study showed a positive large effect size (Cohen’s d = 0.88) of VWT on writing skills. In addition, Year 1 students in the experimental group enjoyed using the VWT software and found it beneficial and helpful in checking the accuracy of their essays including spelling, punctuation, grammar and vocabulary. In light of the research findings, implications and recommendations for future research were outlined.